Virtual reality in tourism: The impact of virtual experiences and destination image on the travel intention - Komsit Kieanwatana; Rattawut Vongvit (Results in Engineering)
This research focuses on the growing significance of virtual reality (VR) in the tourism industry. The COVID-19 pandemic significantly disrupted Thailand's tourism sector, reducing foreign tourist arrivals and challenging traditional tourism models. However, this crisis created opportunities for technological innovation, particularly VR, which has the potential to enhance travel intention by offering immersive, virtual experiences that promote destination appeal and accessibility, even to those unable to travel physically. The study aimed to explore the relationships between virtual experiences, destination images, and travel intention by examining the positive impact of VR on travelers' decision-making processes. The data analysis was conducted using PLS-SEM. This study employed a well-structured research model featuring an instrument with 36 items distributed across 12 constructs to validate the hypotheses. The survey, conducted and collected via Google Forms, involved 400 participants. The analysis outcomes supported 17 of the 20 hypotheses. The R2values of 0.728, 0.959, and 0.704 of the variances in travel intention, virtual experience, and destination image, respectively, demonstrate strong predictive power for each variable. The study suggests strong evidence for these specific associations in the context of virtual experiences, destination images, and their influence on travel intention. This study reveals that virtual experiences and destination images significantly enhance travel intention, highlighting VR's potential as a powerful tool for destination marketing. The findings underscore the importance of accessible information, high-quality content, novelty, and sensory stimulation in creating immersive virtual experiences and the role of recognition in fostering a favorable destination image, though the effects of safety and recognition warrant further investigation.